Partisan cycles and pre-electoral uncertainty - Michael Berlemann; Gunther Markwardt (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
Rational partisan theory of political business cycles suggests differences in inflation under left-wing and right-wing governments. It also suggests temporary post-electoral booms after election of left-wing governments and temporary recessions after election of right-wing ones. However, the core hypothesis that post-electoral booms and recessions depend upon the degree of pre-electoral uncertainty has rarely been tested. Using pre-electoral polling data, we provide empirical evidence in favor of the hypothesis of the existence of rational partisan cycles. We also show that - in line with most previous empirical studies - there is little evidence for partisan cycles under adaptive expectations.
Keywords: E32; 330; partisan theory; political business cycles; Politischer Konjunkturzyklus; Wahlverhalten; Erwartungstheorie; Schätzung; Theorie; OECD-Staaten